Dioscin elicits anti‐tumour immunity by inhibiting macrophage M2 polarization via JNK and STAT3 pathways in lung cancer. Issue 16 (2nd July 2020) - Cui, Luyun; Yang, Guangdie; Ye, Jiani; Yao, Yinan; Lu, Guohua; Chen, Junjun; Fang, Liangjie; Lu, Shan; Zhou, Jianying
Abstract: Tumour‐associated macrophage (TAM) is an important component in tumour microenvironment. Generally, TAM exhibits the function of M2‐like macrophage, which was closely related to angiogenesis and tumour progression. Dioscin, a natural steroidal saponin, has shown its powerful anti‐tumour activity recently. However, the mechanism of dioscin involved in immune regulation is still obscure. Here, we observed dioscin induced macrophage M2‐to‐M1 phenotype transition in vitro and inhibited IL‐10 secretion. Meanwhile, the phagocytosis of macrophages was enhanced. In subcutaneous lung tumour models, dioscin inhibited the augmentation of M2 macrophage populations. Furthermore, dioscin down‐regulated STAT3 and JNK signalling pathways in macrophages in vitro. In BMDMs, activating JNK and inhibiting STAT3 induce macrophages to M1 polarization while inhibiting JNK and activating STAT3 to M2 polarization. Additionally, condition mediums from dioscin‐pre‐treated macrophages inhibited the migration of 3LL cells and the tube‐formation capacity of HUVECs. What's more, dioscin‐mediated macrophage polarization inhibited the in vivo metastasis of 3LL cells. In conclusion, dioscin may act as a new anti‐tumour agent by inhibiting TAMs via JNK and STAT3 pathways in lung cancer.